Ensuring The Best Interests of the Child in Divorce Judgments Through the Lens of Maslaá¸£ah Principles - Anshori, Ma'sum; Hayat, Teten Jalaludin (AL-TAHRIR, 2024)
This research analyzes the concept of the child's best interests in divorce judgments from the perspective of the principle of maslahah, with a focus on Verdict Number 225/Pdt.G/2023/PA.Bkls. The study aims to explore how court decisions consider the welfare of the child in the context of divorce, particularly concerning custody and post-divorce financial arrangements. The analytical approach encompasses legal aspects and judicial considerations related to the principle of maslahah. The identified academic problem is the ambiguity in applying the best interests of the child principle in divorce judgments in Indonesia, which often overlooks the aspect of maslahah. The research findings indicate that although the principle of maslahah is frequently mentioned, its implementation is still limited and requires enhancement in judicial practice. This study provides an in-depth understanding of the implementation of the child's best interests in the context of divorce and recommends improvement measures to effectively protect the rights and interests of children in the future. This research is expected to guide wise decision-making among legal practitioners and judicial institutions in handling divorce cases involving children.